Neosemantization of Word NISHCHEBROD in Modern Russian Speech - N. G. Babenko; N. E. Likhina (Научный диалог, 2019)
The functional-semantic specificity of a word nishchebrod in its original and modern meaning and usage is considered. The sources of the factual material of the study are normative and non-normative linguistic dictionaries, the National Corpus of the Russian Language, as well as metalanguage (reflexive) statements presented in the speech space of the Russian Internet, the object of which is the noun nishchebrod . The article analyzes the practice of lexicographic description of the word, provides necessary historical and cultural information about begging in Russia. The research is conducted in line with the semasiological approach to semantic derivation as a kind of secondary nomination. Special attention is paid to the development of semantic differentiation of canonical and actual for modern times meanings of the noun nishchebrod . Its paradigmatic context and lexical valences explicated in the discourse of the Russian Internet are considered. The conditionality of the emergence of neosemant nishchebrod by extralinguistic causes are stated - namely socio-economic, psychological and cultural conditions of existence of the Russian society in the first decade of the 21st century. Nominative, functional, derivational, stylistic correspondences and inconsistencies between the native Russian word nishchebrod and fashionable Anglo-Americanism loser are revealed. Conclusions ae made on incomplete and non-total synonymy of words nishchebrod and loser , on the possibility of the formation of the bipolar structure of the core of the concept “ nishchebrod .”